Enhanced Visible‐light Photocatalytic Dye Degradation Ability of CdS/O‐CNTs Nanocomposites. Issue 35 (16th September 2022) - Wen, Xiaorong; Feng, Jiaping; Zhang, Juan; Fu, Hongquan; Gao, Hejun; Wang, Jinhua; Liao, Yunwen
Abstract: The rapid developpment of industrialization and urbanization has caused extensive environmental pollution, especially water pollution. Here, a bud‐like shaped CdS (cadmium sulfide), with O‐CNTs (oxidized multiwalled carbon nanotubes) homogeneously embedde (BCO), were synthesized by a facile hydrothermal process. The surface properties of the composites and the photocatalytic performances were studied systematically. The photocatalytic degrading anionic dye Methyl orange (MO) and cationic dye Rhodamine B (RhB) under visible light (λ≥420 nm) unveiled that BCO nanocomposites exhibited much better photocatalytic decolorization activity than bud‐like shaped CdS. Due to the delaying time of electron recombination to the hole and the participation of holes (h + ) and⋅superoxide radicals (⋅O2 − ) by loading O‐CNTs, BCO‐3 wt% could decolorize 98.5 % RhB in 30 min and 95.5 % MO in 90 min, implying potential applications prospect. Abstract : Bud‐like shaped CdS (Cadmium Sulfide)/O‐CNTs (oxidized multiwalled carbon nanotubes) nanocomposites were prepared through hydrothermal methods for the degradation of organic pollutants by visible‐light irradiation. Under visible‐light irradiation, BCO nanocomposites demonstrated prominent activities for the degradation of Rhodamine B and Methyl orange, with the introduction of O‐CNTs into nanocomposites greatly increasing the activity of pure BC. This activity enhancement for the nanocomposites could be mainly attributed to the delaying time of electron recombination to the hole and the participation of holes (h + ) and superoxide radicals (⋅O2 − ). Therefore, a new and simple strategy was provided to realize the target contaminants in water by photocatalytic degradation technology.